Protein-mediated hydroxyapatite composite layer formation on nanotubular titania - Utku, Feride Sermin; Yuca, Esra; Seckin, Eren; Goller, Gultekin; Karatas, Ayten Yazgan; Urgen, Mustafa; Tamerler, Candan (ICE PUBLISHING, 2015)
Realising controllable interactions at the bio-nanomaterial interfaces are vital in developing next-generation engineered implant materials. Titanium-based implants are key materials in biomedical engineering due to excellent bulk mechanical properties and biocompatibilities. Advanced bio-interfaces resolving nanostructured modulated surfaces that allow manipulation with the biological molecules is one of the keys to enhance favourable interactions with the surrounding biological species. Here, we developed a protein-mediated hydroxyapatite composite layer on nanotubular titania surface. Green fluorescence protein, engineered to contain hydroxyapatite binding peptides (GFPuv-HABP), was co-deposited with the hydroxyapatite precursors onto the titania nanotubes that are formed by anodisation. Ordered titanium dioxide nanotubular surfaces were coated with hydroxyapatite at physiological pH and temperature using simulated body fluid and pulsed electrochemical cathodisation. The hydroxyapatite deposit interdigitated into the nanotubes, producing a metal oxide-mineral composite. The engineered GFPuv-HABP protein was then self-assembled on the hydroxyapatite, forming a bio-modulated interface. Additionally, the engineered proteins were co-deposited with the precursor ions of hydroxyapatite mineral on the nanotubular titania plate. Bio-mediated assembly resulted in formation of a hybrid composite as an integrated interface on the nanotubular surface. Biomolecular assisted fabrication of hybrid composite interface on metal oxide substrate offers wide range of opportunities to design novel interfaces.
Keywords: biocompatible; biointerface; biomaterial; CALCIUM-PHOSPHATE COATINGS; IN-VITRO; ELECTROCHEMICAL DEPOSITION; SURFACE MODIFICATION; MATERIALS SCIENCE; DENTAL IMPLANTS; OXIDE NANOTUBES; SUBSTRATE; PEPTIDES; CELL; Engineering